The Influence of Product Reviews and Ratings on Purchase Decisions in Shopee E-Commerce - Rohman, Muhamad Fahmi Aulia; Andriana, Myra; Kusumajaya, Robby Andika (Pusat Riset dan Inovasi Nasional, 2026)
The development of e-commerce, particularly Shopee, has driven changes in consumer geste in making purchase opinions, which are now largely told by digital information similar as product reviews and conditions. still, there's still query regarding the extent to which these two factors affect consumer pur- chasing opinions. This study aims to dissect the influence of product reviews and product conditions on copping opinions in Shopeee-commerce. This exploration uses a quantitative approach with a check design. The subjects of the study are Shopee druggies who have made purchases. Data were collected through the distribution of questionnaires and anatomized using multiple direct retrogression ways to discourage- mine the effect of each variable.The results show that product reviews have a posi- tive and significant effect on copping opinions, with a significance value of< 0.05. Product conditions also have a positive and significant effect on copping de-cisions, with a significance value of< 0.05. contemporaneously, both variables have a significant influence on copping opinions, with a measure of determination of roughly 65, indicating that utmost copping opinions are told by product reviews and ratings. The conclusion of this study is that product reviews and product conditions play an important part in impacting consumer copping decisions on Shopee. The better the reviews and the advanced the conditions given, the lesser the liability that consumers will make a purchase.